Living Conditions Index (LCI) in the Territory of the Citizenship Reform - Mato Grosso do Sul. - Casimiro, Leonardo Alves de Oliveira; Vilpoux, Olivier François (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The research aimed to evaluate the quality of life for residents of the territory of the Reformation. Profile, sources of income, level of education, participation in associations were analyzed. The results were compared among family farmers, not farmers and not producers. The survey was conducted through a questionnaire administered by MDA, with project funded by CNPq, with 250 producers in the territory of the reform. It was possible to identify a significant number of producers who need to supplement income outside. Despite respondents present a low level of education, they were satisfied. It is possible to estimate that the low level of schooling causes a lack of critical approach which can hinder the implementation of policies to improve education. Entres youth education level is improving and many teens have already surpassed the level of parental education. The age groups showed a predominance of older people. The resignation of the young by agricultural activities and the pursuit of higher education in the city are reasons that give rise to the abandonment of rural areas. Because of the importance of family farming in social role and the generation of wealth of the state economy, family farming needs attention from the government and companies to improve education and reduce the exodus of young people to the city.